Career guidance and employment management system - Seng, Kasem; Zeki, Akram M. (IEEE, 2014)
This paper presents a designing of a web based system for Career Guidance and Employment Management System (CGEMS). Basically, CGEMS is tries to help a user who is looking for career advice guidance, or looking for their opportune job. CGEMS tries to make one place where student, job seeker, career advisor or consultant, and various company or organization can meet and help. In order to help the users to determine their best career choice, this system also offers some tests or quizzes that are related to such career and the user personality which will be useful for the career path. Furthermore, users of CGEMS such as company or organization can post a job description, when they look for employee.